Social media overload, exhaustion, and use discontinuance: Examining the effects of information overload, system feature overload, and social overload. Issue 6 (November 2020) - Fu, Shaoxiong; Li, Hongxiu; Liu, Yong; Pirkkalainen, Henri; Salo, Markus
Highlights: System feature overload, information overload and social overload lead to individuals' social media fatigue. Social media fatigue leads to individuals' discontinuous usage of social media. System feature overload is associated with information overload and social overload. Stressor–strain–outcome (SSO) framework can help explain individuals' social media discontinuance behavior from the overload perspective. Abstract: While users' discontinuance of use has posed a challenge for social media in recent years, there is a paucity of knowledge on the relationships between different dimensions of overload and how overload adversely affects users' social media discontinuance behaviors. To address this knowledge gap, this study employed the stressor–strain–outcome (SSO) framework to explain social media discontinuance behaviors from an overload perspective. It also conceptualized social media overload as a multidimensional construct consisting of system feature overload, information overload, and social overload. The proposed research model was empirically validated via 412 valid questionnaire responses collected from Facebook users. Our results indicated that the three types of overload are interconnected through system feature overload. System feature overload, information overload, and social overload engender user exhaustion, which in turn leads to users' discontinued usage of social media. This study extends current technostress research by demonstrating the value of the SSO perspective in explaining users' social media discontinuance.